Afraid to die - Jackson, Lisa (Jackson, Lisa. Selena Alvarez/Regan Pescoli novels., 2012)
Detectives Selena Alvarez and Regan Pescoli investigate after two women's bodies are found frozen and deliberately displayed with both victims wearing a piece of Selena's jewelry.